The influence of discus mass on performance-determining variables - Emmerzaal, J.; Hoogerbrugge, T.; Janssen, I. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to investigate the effects of discus mass on two performance-determining variables; timing of acceleration and release velocity. Twelve male discus throwers performed 25 throws with 5 different masses as inertial sensors collected acceleration data of each throw. Release velocity, but not timing of acceleration, was influenced by discus mass. Large differences were seen between skilled and less skilled athletes with regard to timing of acceleration and release velocity. Skilled athletes demonstrated altered timing of acceleration with increased discus mass. No such differences, however, were found between more and less powerful athletes. As a result, the less skilled athletes were more affected by the varying discus mass than the skilled athletes.